The Relationship between Teachers' Teacher Leadership Roles and Organizational Commitment Levels - Ibrahim Colak; Yahya Altinkurt; Kursad Yilmaz (ÜNİVERSİTEPARK Limited, 2014)
The purpose of this research is to determine the relationship between teacher leadership roles and organizational commitment levels of primary, secondary, and high school teachers. This study was designed in survey model. The sample of the study consisted of 280 teachers working in Mugla, Turkey. Participants were selected using disproportionate cluster sampling technique. Data was collected through the application of the Teacher Leadership Scale and Teacher Organizational Commitment Scale. Descriptive statistics, t-test, ANOVA, and Pearson correlation coefficients were used to analyse the data. Based on the findings, teachers' level of performing leadership roles was lower than they consider such roles to be necessary. Teachers consider that the professional improvement dimension of teacher leadership was the most necessary, and should be performed accordingly. This is followed by collaboration among colleagues, and institutional improvement. Teachers also consider that they demonstrate moderate level of commitment. There are significant relationships between teachers' teacher leadership roles and organizational commitment levels.